Examination of four potential new industrial opportunities for the Caribbean Community : report (Redma Consultants TorontoCA, 1982)
Discusses and makes recommendations pertaining to four industries in the Caribbean viz. expansion of vegetable oil processing facilities; production of galvanized sheeting; manufacture of work boots; and manufacture of glue resins. For each industry the study analyzes existing production and determines present and future demand for the product. Where sufficient demand exists, as is the case with the first two industries the study undertakes a preliminary feasibility study which provides basis on which an investment decision could be made.
IDS